Emergence of Novel Superconductivity Near the Boundary between Semiconductor and Semimetal - MATSUBAYASHI, Kazuyuki (The Review of High Pressure Science and Technology, 2025)
The discovery of superconductivity and its novel mechanisms has attracted attention in condensed matter physics. In this article, we review our recent work on pressure-induced superconductivity at the semiconductor-semimetal boundary regions in Ta2NiSe5 and LaOPbBiS3. Ta2NiSe5 is known as the promising candidate for excitonic insulator, and our high-pressure experiments have led to the discovery of superconductivity and a phase diagram covering the transition from the semiconducting to the semimetallic regime. We also report on the pressure-induced superconductivity in the bismuth chalcogenide semiconductor LaOPbBiS3 in the vicinity of the localization threshold.